Patch test–relevant concentrations of metal salts cause localized cytotoxicity, including apoptosis, in skin ex vivo. (15th August 2021) - Zhang, Yan; de Graaf, Niels P. J.; Veldhuizen, Rosalien; Roffel, Sanne; Spiekstra, Sander W.; Rustemeyer, Thomas; Kleverlaan, Cees J.; Feilzer, Albert J.; Bontkes, Hetty; Deng, Dongmei; Gibbs, Susan
Abstract: Background: Metal alloys containing contact sensitizers (nickel, palladium, titanium) are extensively used in medical devices, in particular dentistry and orthopaedic surgery. The skin patch test is used to test for metal allergy. Objective: To determine whether metal salts, when applied to freshly excised skin at patch test–relevant concentrations and using a method which mimics skin patch testing, cause in changes in the epidermis and dermis. Methods: Tissue histology, apoptosis, metabolic activity, and inflammatory cytokine release were determined for two nickel salts, two palladium salts, and four titanium salts. Results: Patch test–relevant concentrations of all metal salts caused localized cytotoxicity. This was observed as epidermis separation at the basement membrane zone, formation of vacuoles, apoptotic nuclei, decreased metabolic activity, and (pro)inflammatory cytokine release. Nickel(II) sulfate hexahydrate, nickel(II) chloride hexahydrate, titanium(IV) bis(ammonium lactato)dihydroxide, and calcium titanate were highly cytotoxic. Palladium(II) chloride, sodium tetrachloropalladate(II), titanium(IV) isopropoxide, and titanium(IV) dioxide showed mild cytotoxicity. Conclusion: The patch test in itself may be damaging to the skin of the patient being tested. These results need further verification with biopsies obtained during clinical patch testing. The future challenge is to remain above the elicitation threshold at noncytotoxic metal concentrations. Abstract : Patch test–relevant concentrations of metal salts applied to excised skin caused epidermis separation at basement membrane zone, formation of vacuoles, apoptotic nuclei, decreased metabolic activity, and (pro)inflammatory cytokine release. Nickel sulfate hexahydrate, nickel chloride hexahydrate, titanium bis(ammonium lactato)dihydroxide, and calcium titanate were highly cytotoxic. Palladium chloride, sodium tetrachloropalladate, titanium isopropoxide, and titanium dioxide showed mild cytotoxicity. The patch test in itself may be damaging to the skin of the patient being tested, indicating that the future challenge is to remain above the elicitation threshold at noncytotoxic metal concentrations.